Hubungan Inisiasi Menyusu Dini dan ASI Eksklusif dengan Stunting pada Baduta Usia 7-24 Bulan - Annisa, Nur; Sumiaty, Sumiaty; Tondong, Henrietta Imelda (Jurnal Bidan Cerdas, 2019)
Stunting can be caused by a variety of factors, such as the implementation of initiation of early breastfeeding which is not appropriate and the provision of breast milk is not exclusive. The purpose of this study was to know the relationship between early breastfeeding initiation and exclusive breastfeeding with stunting in two-year-old infants aged 7-24 months in the work area of Pantoloan Health Center. This type of research was an analytical survey with design cross-sectional. The sample in this study were two-year-old infants aged 7-24 months totaling 57 samples with sampling techniques namely proportional random sampling and data analysis using Chi-Square. The results showed that respondents who experienced stunting were 36.8% and not stunting 63.2%. Respondents who had early breastfeeding initiationn din not tend to experience stunting (79.2%), while respondents who received exclusive breastfeeding tended not to experience stunting (81.0%). The results of the statistical test showed a significant relationship between early breastfeeding initiation and exclusive breastfeeding with stunting with the same p-value of 0.033 (Î±<0.05). The conclusion is that there was a relationship between early breastfeeding initiation and exclusive breastfeeding with stunting. Suggestions for researchers and for health workers to maximize promote and implement early breastfeeding initiations and exclusive breastfeeding for mothers to prevent and minimize the incidence of stunting in children in the future.